An Overview of Bimekizumab for the Treatment of Psoriatic Arthritis: The Evidence so Far - G Oliveira D; Faria R; Torres T (Dove Medical Press, 2021)
Daniel G Oliveira,1 Raquel Faria,2,3 Tiago Torres3,4 1Department of Internal Medicine, Centro Hospitalar e Universitário do Porto, Porto, Portugal; 2Clinical Immunology Unit (UIC), Centro Hospitalar e Universitário do Porto, Porto, Portugal; 3Unit for Multidisciplinary Research in Biomedicine, Instituto de Ciências Biomédicas Abel Salazar – University of Porto, Porto, Portugal; 4Department of Dermatology, Centro Hospitalar e Universitário do Porto, Porto, PortugalCorrespondence: Tiago TorresDepartment of Dermatology, Centro Hospitalar Universitário do Porto, Rua D. Manuel II, s/n, ex-CICAP, Porto, 4099-001, PortugalEmail torres.tiago@outlook.comAbstract: Psoriatic arthritis is a complex and heterogeneous disease with potential significant disability and impaired quality of life. Although in the last decades new treatment options have led to a better management of this disease, there are still significant unmet therapeutic needs. Dual inhibitor antibodies target two different cytokines simultaneously, potentially offering a better disease control. In psoriatic arthritis, there is evidence for a pathogenic role not only of IL-17A but also the structurally homologous IL-17F. It is postulated that differential expression of both in several targets of PsA could account for disparities in clinical response to IL-17A inhibition alone (such as with secukinumab or ixekizumab). Here we review the evidence so far for the use in psoriatic arthritis of bimekizumab, the first humanized monoclonal IgG1 antibody that selectively neutralizes both IL-17A and IL-17F. A Phase 2b trial reports better outcomes over both placebo and IL-17A inhibition alone. Very recently encouraging results from open-label extensions with regards to both safety and maintenance of response were presented. Phase III trials are ongoing with the first results awaited in 2021.Keywords: psoriatic arthritis, psoriasis, bimekizumab, interleukin-17A, interleukin-17F, biologic therapy